Auditory selective attention and performance in high variability phonetic training: The perception of Portuguese stops by Chinese L2 learners - Oliveira, Diana Moreira de (2020)
Tese de Doutoramento em Ciências da Linguagem (Especialidade de Linguística Aplicada)